Comparison of vasodilatory properties between desflurane and sevoflurane using perfusion index: a randomised controlled trial. (December 2020) - Ryu, Kyoung-Ho; Hwang, Sung-Ha; Shim, Jae-Geum; Ahn, Jin-Hee; Cho, Eun-Ah; Lee, Sung-Hyun; Byun, Jae-Hoon
Abstract: Background: The perfusion index (PI), calculated from the photoplethysmographic waveform, reflects peripheral vasomotor tone. As such, the PI serves as a surrogate for quantitative measures of drug-induced vasoconstriction or vasodilation. This study aimed to compare the effect on the PI of desflurane and sevoflurane at equi-anaesthetic concentrations in patients undergoing single-agent inhalation anaesthesia, where equi-anaesthetic dose was based on the known minimum alveolar concentration of these agents. Methods: We randomly allocated patients scheduled for arthroscopic knee surgery to receive either desflurane or sevoflurane general anaesthesia after target-controlled induction of anaesthesia with propofol. Anaesthesia was maintained at age-corrected minimum alveolar concentration 1.0, under neuromuscular block (rocuronium). The PI and haemodynamic data were recorded every minute for 35 min after induction of anaesthesia and after standardised nociceptive stimulation. The primary outcome was PI, compared between the groups over time (repeated-measures analysis of variance). Secondary outcomes included MAP and HR. Results: Sixty-nine participants (mean [range] age: 42 yr [19–65 yr]; 49% females) were assigned to either desflurane ( n =34) or sevoflurane ( n =35). The PI remained higher under desflurane compared with sevoflurane, both before (mean difference [MD]: 3.3; 95% confidence intervals [CIs]: 2.0–4.7; P <0.001) and after tetanic stimulation (MD: 2.8; 95% CI: 2.0–3.7; P <0.001). Higher PI paralleled lower MAP in participants assigned to desflurane anaesthesia ( P <0.001), both before (MD: 8 mm Hg; 95% CI: 4–12) and after nociceptive stimulation (MD: 14 mm Hg; 95% CI: 7–22). HR was similar throughout. Conclusions: These findings suggest that at equipotent doses, desflurane exerts more potent vasodilatory properties and lowers blood pressure by a magnitude potentially associated with harm. Clinical trial registration: NCT03570164.